2015
DOI: 10.1039/c5sc02161h
|View full text |Cite|
|
Sign up to set email alerts
|

Ligand survey results in identification of PNP pincer complexes of iridium as long-lived and chemoselective catalysts for dehydrogenative borylation of terminal alkynes

Abstract: A new, highly active Ir catalyst for dehydrogenative borylation of terminal alkynes (DHBTA) has been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 81 publications
4
43
1
Order By: Relevance
“…7 Platinum is rarely mentioned in the field of dehydrogenative borylation, but has been shown to catalyse the dehydrogenative borylation of olefins with borane clusters. 10 A slower DHBTA catalysis with a similar scope was reported by Tsuchimoto et al using Zn(OTf ) 2 /pyridine. Alkynylboronates are widely applicable in organic synthesis and their use has recently been reviewed.…”
supporting
confidence: 63%
“…7 Platinum is rarely mentioned in the field of dehydrogenative borylation, but has been shown to catalyse the dehydrogenative borylation of olefins with borane clusters. 10 A slower DHBTA catalysis with a similar scope was reported by Tsuchimoto et al using Zn(OTf ) 2 /pyridine. Alkynylboronates are widely applicable in organic synthesis and their use has recently been reviewed.…”
supporting
confidence: 63%
“…This reaction showed high chemical selectivity, and no other side reactions, such as hydrogenation and hydroboration, occurred . Later, the authors investigated the ligand effect and found that an unsymmetrical PNP‐supported iridium complex could also efficiently catalyzed this reaction with only a 0.025 mol % loading of catalyst . Good to excellent yields were obtained for aryl, alkyl and silyl acetylenes, even including propargyl derivatives and 1,6‐enynes.…”
Section: Formation Of Spc−heteroatom Bondsmentioning
confidence: 99%
“…Alkynyl boronates can be prepared from monovalent alcohols [10,11], but due to their increased hydrolytic stability the incorporation of bifunctional chelating alcohols, in particular 1,2-dihydroxy compounds, is highly preferred. Thus, the bivalent alcohols introduce a bridging backbone leading to improved stability, and the scope of 1,2-diols employed for alkynyl boronate esters includes pinacol ( 1 ) [12,13,14,15,16,17,18,19], catechol, ( 2 ) [20,21,22], and ethylene glycol ( 3 ) [23,24], Scheme 1. These compounds 1 – 3 may also be considered as boron substituted heterocycles and can be viewed as derivatives of the parent 1,3,2-dioxaborolane.…”
Section: Introductionmentioning
confidence: 99%